Reconceptualising ‘caring’ in e-tutor-student interactions during the Covid-19 pandemic in an ODeL university in South Africa - Shange, Thembeka (Critical Studies in Teaching and Learning, 2023)
In South Africa and elsewhere, the outbreak of Covid-19 in 2020 and the lockdown regulations forced both academics and students to adapt to a new reality of fully online modules and assessments. This catapulted relations in higher education into the spotlight. The concern of this paper is how e-tutors in an Open Distance e-Learning (ODeL) university in South Africa have enacted care in online interaction with the students during this period. Available research focuses on online interaction; however, there is a paucity when it comes to care cultivated by e-tutors on students to increase online interactions during the covid-19 pandemic. Through the lens of Relational Care, this paper seeks to reconceptualise care during e-tutor-student interaction in one of the English modules at a mega South African ODeL university. Data were collected through a survey completed by e-tutors (n = 8) and lecturers (n = 4) of one of the English modules at this university. Through content analysis, patterns and categories emanating from the data were extracted. Findings indicated that e-tutors and lecturers had minimal understanding of how to enact care in this environment during the covid-19 pandemic. Future research should focus on how to manage student online interaction in an OdeL environment during crises.